The act of being teacher in continuing construction - Antunes, Denise Dalpiaz (2018)
This text aims to contribute with some reflections about the continuing formation of teachers, in addition to the initial formation, in the paradigmatic proposal of continuing education, throughout the personal life of the teacher, presenting theoretical constructs that point to so many possibilities of self - formation in search of self – knowledge of the professionals that form the basis of the human formation of other human beings. In addition, the article presents a continuing education model considered to be efficient by the need for refresher training, based on pedagogical workshops with cooperative work among peers. A proposal for a government that, although it has not constituted itself as a possibility of public policy of teacher formation in Brazil, which ends up emphasizing the lack of incentives and social awareness for the profession of Being Teacher, pointed out the possibility of renewed practices based on formations in the school locus, as highlighted by the great majority of participating teachers.